PENGARUH PROMOSI MEDIA SOSIAL TERHADAP KEPUTUSAN BERKUNJUNG WISATAWAN KE KAMPUNG EROPA LEMBAH HARAU - Wal Adzan, M. Rafi; Putra, Trisna (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Research on the Effect of Social Media Promotion in the European Village of Lembah Harau stems from the problem that the authors found, namely the lack of promotion through social media in the European Village. Promotion through social media is very important because it is useful for introducing or reaching out further to tourists so that they can improve their decision to visit Kampung Europe. And this research is also based on the needs of the Tourism and Youth Office of the Limapuluh Kota Regency in recording and increasing visits to tourist objects. This type of research uses quantitative research methods with a causal associative approach. The population of this study amounted to 3,120 and this research sample was taken using a non-probability sampling technique with a sample of 100 people. The instrument used in this study was a questionnaire that was structured using a Likert scale. The data in the study were processed with the help of the SPSS version 20 program. The analysis technique in this study was quantitative descriptive analysis method. The results showed that: (1). Social Media Promotion Variable (X) obtained results as much as 57% with the category strongly agree. (2). The Visiting Decision Variable (Y) obtained results as much as 48% in the category of agreeing. The results in this study that through simple linear regression test obtained F count 70,305 with Sig 0.000> 0.05 then the regression model can be used. Then HA is accepted and HO is rejected.Keywords: Social Media Promotion, Visit Decision, European Village